KONTROL DIRI DAN STRATEGI COPING TERHADAP PENGUNGKAPAN DIRI DALAM APLIKASI TIKTOK PADA REMAJA - Michelle Sandya Luchy, Vania; Nurhidayah, Siti; Duhita Pramintari, Ratna (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2023)
The Tiktok application is currently undergoing a change, which was originally a medium of entertainment for singing and dancing, which has become an arena for self-disclosure about their talents. Gradually, many self-disclosures seek sensation, so that many social judgments appear that are not good. This study aims to determine the effect of self-control, coping strategies, on self-disclosure through the Tiktok application in adolescents. This research method uses a quantitative design. The research subjects were teenagers in South Tambun District. The number of samples is 120 people. Sampling is done by way of Quota Sampling. The research instrument used self-control scale, coping strategy scale, and self-disclosure scale. Data collection techniques using interviews, observation and psychological scales. Data analysis test using Rank Spearman correlation and multiple linear regression analysis. The results of the descriptive analysis show that self-control variables are in the high category of 93 (77.5%), coping strategy variables are in the high category of 108 (90%), self-disclosure variables are in the high category of 78 (65%). The results of data analysis showed (F test) of 0.000b (P <0.05) there was a significant effect between self-control variables and coping strategies on selfdisclosure with a relative contribution of 53.2%.